Exploring critical success factors for TQM implementation using interpretive structural modelling approach: extract from case studies. (2017) - Kumar, Vimal; Sharma, R.R.K.
The purpose of this paper is to explore the critical success factors for TQM implementation from the real case analysis. Eisenhardt (1989) seminal article on 'Building theories from case study research' has motivated researchers from diverse areas to adopt case study methodology to build concepts and theories and case research on TQM implementation concepts is no exception. From extant literature review and many other sources of information, these critical success factors have been carried out. The successful TQM implementation set comprised seven companies. Interpretive structural modelling (ISM) approach has been applied in this study. From this case analysis, we found 18 success factors. This paper aims to identify and develop the structural relationship among different critical success factors for successful implementation of TQM. The findings of the study provide hierarchy level of all 14 factors from top to bottom level and critical input for TQM implementation with firms being more proactive and better prepared for TQM implementation.